Cross‐Jurisdictional Income Shifting by U.S. Multinationals: Evidence from International Bond Offerings - Newberry, Kaye J.; Dhaliwal, Dan S. (Journal of Accounting Research, 2001)
We examine whether tax incentives influence where U.S. multinationals locate their interest deductions worldwide. Our sample includes international bond offerings by U.S. multinationals during 1987–1997 denominated in the currencies of Australia, Canada, France, Germany, Italy, Japan, or the United Kingdom. Our results suggest that U.S. multinationals’ debt location decisions take into account the effect of jurisdiction‐specific tax‐loss carryforwards and binding foreign tax credit limitations on the value of debt tax shields. Our results are also consistent with U.S. multinationals locating interest deductions in different tax jurisdictions as a mechanism to achieve tax‐motivated income shifting.